Torture of the duke of Nemours (engraving) - Auteur inconnu (Wikimedia Commons, 1883)
Notice iconographique issue de Wikimedia Commons. Titre: Torture of the duke of Nemours (engraving). Torture of the duke of Nemours (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons